THE IMPORTANCE OF FURFUROL IN THE NATIONAL ECONOMY (Scientific journal of the Fergana State University, 2024)
Production of furfural-based briquettes, chemical properties, fields of their use, properties of polymermaterials based on furan briquettes are presented.